High fish intake rich in n-3 polyunsaturated fatty acids reduces cardiovascular disease incidence in healthy adults: The ATTICA cohort study (2002-2022) - Critselis, Elena; Tsiampalis, Thomas; Damigou, Evangelia; Georgousopoulou, Ekavi; Barkas, Fotios; Chrysohoou, Christina; Skoumas, John; Pitsavos, Christos; Liberopoulos, Evangelos; Tsioufis, Costas; Sfikakis, Petros P.; Panagiotakos, Demosthenes (Frontiers in Physiology, 2023)
Background: The long-term effects of high fish intake rich in n-3 fatty acids for deterring cardiovascular disease (CVD) and related adverse outcomes in healthy individuals have not been yet elucidated. Purpose: To evaluate the association between total seafood, as well as small fish, intake on 10- and 20-year CVD incidence and mortality in healthy adults. Methods: A prospective cohort study (n = 2,020) was conducted in healthy community dwelling adults in Athens, Greece, selected following age- and sex-based random multistage sampling (mean ± SD age at baseline: 45.2 ± 14.0 years). Seafood (high (>2 servings/week) vs. low (≤2 servings/week) intake), including small fish rich in n-3 fatty acids (high (>1 serving/week) vs. low (≤1 serving/week) intake), consumption was evaluated by semi-quantitative food frequency questionnaire at baseline. The occurrence of non-fatal and/or fatal CVD events (ICD-10) was assessed during 10- and 20-year follow-up periods. Results: Only 32.7% and 9.6% of participants had high seafood and small fish intakes, respectively. Participants with high seafood intake had 27% decreased 10-year CVD risk (adj. HR:0.73; 95% CI:0.55-0.98) and 74% lower attributable mortality (adj. HR:0.26; 95% CI:0.11-0.58). Participants with high seafood intake also sustained a 24% lower 20-year risk of CVD mortality (adj. HR: 0.76; 95% CI: 0.55-0.98). Moreover, participants with high small fish intake had a lower 10-year CVD risk and 76% decreased risk of 10-year CVD mortality (adj. HR:0.24; 95% CI:0.06-0.99), even among normotensive individuals (adj. HR:0.31; 95% CI:0.13-0.73). When analogous analyses focused on 20-year CVD incidence and mortality, similar but not significant associations were observed (all p-values >0.10). Conclusion: High intake of seafood, and particularly small fish rich in n-3 fatty acids, was associated with a lower risk of 10-year fatal and non-fatal CVD. Thus, public health interventions aimed at enhancing small fish consumption may most effectively deter long-term CVD outcomes, particularly among low risk normotensive individuals.